Assessing Your Strengths – Hungarian Validation of the 24-Item Values in Action Inventory of Strengths on a Large Sample - Virág ZÁBÓ; Attila OLÁH; Dávid ERÁT; András VARGHA (European Journal of Mental Health, 2023)
Introduction: Several studies have shown the inconsistent factorial structures of the Values in Action Inventory of Strengths between cultures. Aims: This paper describes an adapted Hungarian version of the 24-item Values in Action Inventory of Strengths for adults. Methods: Participants in three online self-report questionnaire-based crosssectional studies (Sn = 10,911) filled in the 24-item Values in Action Inventory of Strengths, the Global Well-being Scale, Huppert’s and Diener’s Flourishing Scales, and the Positivity Scale. Results: The exploratory factor analyses provided evidence for four factors: Wisdom and Knowledge; Humanity; Temperance; and Spirituality and Transcendence. The scales showed excellent internal consistency values in each study. The confirmatory factor analyses of the subsamples also showed a good fit. Low discriminant but excellent content validity was proved. Participants rated themselves highest on Humanity and lowest on Temperance. Women reported significantly higher values on both the Humanity and the Spirituality and Transcendence virtue scales than did men. The Wisdom and Knowledge virtue showed a positive correlation with education level. Among those living alone, Humanity was significantly lower, while the level of Humanity among married people stood significantly higher than in any other group. Conclusion: Our results suggest that the Hungarian version of the 24-item Values in Action Inventory of Strengths for adults serves as a suitable measure for assessing character strengths and virtues.